2012
DOI: 10.1097/cej.0b013e32834c9c0f
|View full text |Cite
|
Sign up to set email alerts
|

A combination of resveratrol and melatonin exerts chemopreventive effects in N-methyl-N-nitrosourea-induced rat mammary carcinogenesis

Abstract: The neurohormone melatonin is primarily involved in the regulation of circadian rhythms, but also acts as an antioxidant and anticarcinogenic agent, especially in breast cancer. Resveratrol (3,5,4'-trihydroxy-trans-stilbene) is a widely known polyphenolic agent from red wine, which has been shown to exert antioxidant, anti-inflammatory and anticarcinogenic effects. The objective of this study was therefore to investigate the effects of melatonin in combination with resveratrol in a rat model of experimental ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…The treatment reduced tumor incidence, significantly decreased invasive and in situ carcinomas and prevented the food intake reduction resulting from carcinogen application in rats (Kisková et al, 2012). However, the reason for the superior effect of resveratrol/melatonin remains unknown.…”
Section: Synergistic Effects Of Melatonin and Resveratrolmentioning
confidence: 99%
“…The treatment reduced tumor incidence, significantly decreased invasive and in situ carcinomas and prevented the food intake reduction resulting from carcinogen application in rats (Kisková et al, 2012). However, the reason for the superior effect of resveratrol/melatonin remains unknown.…”
Section: Synergistic Effects Of Melatonin and Resveratrolmentioning
confidence: 99%
“…Some recent studies have also evaluated the combinatorial effects of resveratrol with other naturally occurring and chemotherapeutic agents, suggesting that resveratrol can improve the efficacy of other agents. [2][3][4][5][6][7][8] Indeed, the strategy of using resveratrol in combination with other agents, particularly with chemotherapeutic modalities, may hold clinical promise for cancer management. However, evidence-based scientific evaluations in appropriate models are needed to show the efficacy of resveratrol in combination with other agents.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that estrogen receptor β (ERβ) can inhibit ligand-mediated PPARγ-transcriptional activity and subsequently block PPARγ-induced gene expression. As we reported before, NMU-induced tumors in Sprague-Dawley rats show strong positivity for both ERα and ERβ [55] which can interfere with thiazolidinedione activity. Neither higher nor lower ROS dose significantly altered tumor growth with the exception of decreased tumor frequency per group after higher ROS dose (by 44%).…”
Section: Discussionmentioning
confidence: 77%